Prototyping and Validating the CORA Ontology: Case Study on a Simulated Reconnaissance Mission - Neto, Antonio; Silva, Jonatas; Barreto, Marcos (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Ontologies play an important role across several domains as they represent and define categories, properties and relationships among concepts, data and entities existing in those domains. Specially in Robotics, ontologies can be used as a standard way to represent and share knowledge and reasoning among autonomous agents. CORA (core ontology or robotics and automation) is a standard ontology developed by the IEEE ORA working group mapping main concepts and axioms from the robotics and automation (R&A) domain. After CORA has been approved as an official IEEE standard, ORA was split in different sub-groups addressing, among other topics, task representation (RTR) and autonomous robots architectures (AuR). This paper presents a simulation study on a multirobot reconnaissance application intended to serve as proof-ofconcept on the feasibility of the CORA ontology and its related architecture. We show how robots and tasks are represented and dynamically mapped into the ontology, as well discuss some technical aspects of our simulation when dealing with the proposed architecture. Our results show the proposed ontology (CORA) and its associated reference architecture (ROA) are able to be correctly mapped during application runtime.